Analysis of factors affecting Labor Demand in Non-Government Sector - Ganiev Bakhtiyor Zulfikor ugli; Karimova Latofat Sadullayevna; Shomurodov Tokhir Boymurod ugli; Quziyeva Gulnoza Rashidovna; Rahmonov Bekzod Sharibjon ugli (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
The article analyzes the statistics on the factors affecting the demand for labor and makes recommendations and suggestions to increase the demand for labor using the OLS method. In contrast to previous studies, this research seeks to analyze impact of various factors on employment in non-government sector. An increase of one percent in the interest rate will reduce the number of workers in the private sector by 0.307 units. The inverse relationship between interest rate and the number of workers in the real sector obtained and it is more statistically significant than results of previous papers